Repensando a formação de profissionais de saúde à luz dos movimentos de mudança - Moraes, Bibiana Arantes (2016)
National Curriculum Guidelines (NCG) and reorientation programs of health professionals’ formation guide the health education in Brazil and the curriculum construction of graduation courses. They still intent to build professionals compromised with the health system and the community. This study aims to understand the health formation from changing movements. The methodology was the exploratory social research with qualitative approach. It has been done literature review, documentary research of the Nursing, Pharmacy, Medicine, Nutrition and Odontology Course’s Pedagogical Project (CPP) of a federal institution and interview with coordinators of studied courses in order to know the process of health formation. All data were submitted to content analysis in thematic mode. While making analysis, categories demonstrating the CPP show proposals according to the legislation that guides the health formation in Brazil emerged. Regarding the interviews it was reported several changes in health formation due to the reorientation programs’ influence in studied courses. Among them stands out: changes in studied curriculums, in multi-professional teams work, in pedagogical approach adopted by professors, teacher’s developmental, enhance of education, research and extension activities, increase of primary care in practice and subjects and interdisciplinary and integration among the courses. In conclusion, the studied health courses are in transition phase to changes proposed by NCG and guided in a transforming education.